Atomic force microscopy in cell biology - Jena, Bhanu P.; Heorber, J. K. Heinrich (San Diego, CA Academic Press, 2002)
This is the first book to cover the history, structure, and application of atomic force microscopy in cell biology. Presented in the clear, well-illustrated style of the Methods in Cell Biology series, it introduces the AFM to its readers and enables them to tap the power and scope of this technology to further their own research. A practical laboratory guide for use of the atomic force and photonic force microscopes, it provides updated technology and methods in force spectroscopy. It is also a comprehensive and easy-to-follow practical laboratory guide for the use of the AFM and PFM in biological research.--Provided by publisher.
Local probe techniques / J.K. Heinrich Hèorber -- The atomic force microscope in the study of membrane fusion and exocytosis / Bhanu P. Jena and Sang-Joon Cho -- Atomic force microscope imaging of cells and membranes / Eric Lesniewska ... [et al.] -- Measuring the elastic properties of living cells by the atomic force microscope / Manfred Radmacher -- Cell adhesion measured by force spectroscopy on living cells / Martin Benoit -- Molecular recognition studies using the atommic force microscope / Peter Hinterdorfer -- The biophysics of sensory cells of the inner ear examined by atomic force microscopy and patch clamp / Matthias G. Langer and Assen Koitschev -- Biotechnological applications of atomic force microscopy / Guillaume Charras, Petri Lehenkari, and Mike Horton -- Cellular membranes studied by photonic force microscopy / Arnd Pralle and Ernst-Ludwig Florin -- Methods for biological probe microscopy in aqueous fluids / Johannes H. Kindt ... [et al.] -- Supported lipid bilayers as effective substrates for atomic force microscopy / Daniel M. Czajkowsky and Zhifeng Shao -- Cryo-atomic force microscopy / Sitong Sheng and Zhifeng Shao -- Conformations, flexibility, and interactions observed on individual membrane proteins by atomic force microscopy / Daniel J. Mèuller and Andreas Engel -- Single-molecule force measurements / Aileen Chen and Vincent T. Moy -- Forced unfolding of single proteins / S.M. Altmann and P.-F. Lenne -- Developments in dynamic force microscopy and spectroscopy / A.D.L. Humphris and M.J. Miles -- Scanning force microscopy studies on the structure and dynamics of single DNA molecules / Giampaolo Zuccheri and Bruno Samorá
Includes bibliographical references and index.
Keywords: Cytological Technique; Microscopy, Atomic Force -- Methods; Atomic force microscopy; Cytology -- Techniques; Electronic books